The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1414-49802010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Judiciarização do privado e violência contra a mulher

Abstract: Este trabalho apresenta alguns dos paradoxos presentes na Lei Maria da Penha, tendo como referentes teóricos as recentes análises sobre os processos de jurisdiciarização da vida privada. A mencionada Lei trata sobre relações que por muito tempo foram consideradas fora do espaço regulatório do Estado e tem por objetivo principal erradicar e punir as formas de violência doméstica contra a mulher. Os paradoxos, aos que fazemos referência, apresentam-se tanto no grau de ampliação dos processos de criminalização, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 3 publications
0
7
0
10
Order By: Relevance
“…This perception is socially shared in popular sayings such as "nobody can do any good between man and wife", thereby clarifying the social understanding that marital problems are intimate, should not be discussed publicly, nor should they be objects of intervention (21) . The findings from the study also confirm those found in a survey conducted in the state of Espírito Santo, Brazil, in which men agreed that marital violence should be resolved in the domestic environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This perception is socially shared in popular sayings such as "nobody can do any good between man and wife", thereby clarifying the social understanding that marital problems are intimate, should not be discussed publicly, nor should they be objects of intervention (21) . The findings from the study also confirm those found in a survey conducted in the state of Espírito Santo, Brazil, in which men agreed that marital violence should be resolved in the domestic environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, one of the main achievements of the feminist movement concerning these abuses was the judicial interference in the private space, which consists of using the police power of the State to intervene in the relations of the private space (21) . The Maria da Penha Law is the most expressive mechanism of this juridical conception by criminalizing domestic and family violence against women (21) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, thirty-two years after the first WPPS was deployed, the service is not available at night, on holidays, and on weekends, which hinders access to a specialized and qualified service to meet this demand and weakens the idea of protection and reception brought with the creation of WPPS. Therefore, it is a setback to have to register a formal complaint of domestic violence during police after-hours, as WPPS were an alternative to this service model, which often prevented, diminished, and disqualified the situations of violence experienced by women, reinforcing macho and oppressive positions 6,7,25 .…”
Section: Flagrante Delictomentioning
confidence: 99%
“…The results also revealed that the women who sought the after-hours service had the most visible bruises, required hospitalization and referral to the IML, thus denouncing the intensity of the abuse and the severity of the complaints. Studies based on urgent and emergency health services point out that, although many women come to work in the daytime, abuse occurs predominantly at night 25 . Women seeking care in more than one service indicates the need to adapt the services of assistance to victims regarding their competences and operating hours 25 .…”
Section: The Severity Of Formal Complaints Registered During After-hoursmentioning
confidence: 99%